1993
DOI: 10.1139/f93-172
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and Maturity of Paired Tanner Crabs, Chionoecetes bairdi, from Shallow- and Deepwater Environments

Abstract: Paired male and female Tanner crabs, Chionoecetes bairdi, in a premating embrace were collected from shallow-(< 13 m) and deepwater (> 150 m) benthic environments by scuba and submersible, respectively. Pubescent females were restricted to shallow water; males grasping them were significantly smaller than those grasping oldshell multiparous females with eyed embryos in a large, deepwater mating aggregation. Males appeared to select for large sizes among pubescent females, but not among multiparous female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 17 publications
2
47
0
Order By: Relevance
“…larger primiparous female (Table 3) and by the fact that laboratory studies found no sizedifferential copulatory incompatibility of missing limbs and chela/body size. It is commonly accepted that postmolt males do not breed (Conan & Comeau 1986, Stevens et al 1993, but a small number exhibited grasping behavior with juvenile females and other males in the present study. Males with a clean-hard shell will mate in a noncompetitive laboratory situation (Sainte-Marie pers.…”
Section: Genetic Evidence For Multiple Mating Of Femalesmentioning
confidence: 55%
See 2 more Smart Citations
“…larger primiparous female (Table 3) and by the fact that laboratory studies found no sizedifferential copulatory incompatibility of missing limbs and chela/body size. It is commonly accepted that postmolt males do not breed (Conan & Comeau 1986, Stevens et al 1993, but a small number exhibited grasping behavior with juvenile females and other males in the present study. Males with a clean-hard shell will mate in a noncompetitive laboratory situation (Sainte-Marie pers.…”
Section: Genetic Evidence For Multiple Mating Of Femalesmentioning
confidence: 55%
“…The only field study of the mating of pubescent-prirniparous females found no evidence of a size-assortative mating pattern (Sainte-Marie & Hazel 1992). However, in the related Tanner crab Chonoecetes bairdi, Stevens et al (1993) found a weak positive correlation (r = 0.22) between the body size of males and pubescent females in mating pairs.…”
Section: Phasesmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite a wealth of studies on the limits and mechanisms of crustacean reproduction (Gray & Powell 1964, Waddy & Aiken 1990, Paul & Paul 1992, Stevens et al 1993, Sainte-Marie & Lovrich 1994, Prager 1996, Sainte-Marie & Sainte-Marie 1999, few have conclusively demonstrated sperm limitation. This is attributable both to the large number of factors that must be identified to determine if sperm limitation is occurring and to the difficulty of determining the underlying causes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on commercially important species were often undertaken to understand the reproductive biology of a species to avoid over-exploitation, and to estimate the quantitative and qualitative impact of size-selective or gender-selective fisheries on reproductive success (e.g. Stevens et al 1993, SainteMarie & Lovrich 1994, Hankin et al 1997, Moriyasu & Benhalima 1998, MacDiarmid & Butler 1999, SainteMarie et al 2000, Kendall et al 2002.…”
Section: Introductionmentioning
confidence: 99%